2015
DOI: 10.12707/riv14047
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in elderly people integrated in the Long-Term Care domiciliary teams

Abstract: Resumenpp.9-16 Palavras-chave: adesão à medicação; idoso. Resumo Revista de Enfermagem Referência A R T I G O D E I N V E S T I G A Ç Ã O ( O R I G I N A L ) Adesão do regime terapêutico medicamentoso dos idosos integrados nas equipas domiciliárias de Cuidados ContinuadosMarco contextual: El aumento de las enfermedades y las comorbilidades implica la polimedicación, que puede interferir en la adhesión al ARTM (régimen terapéutico de medicamentos) de los ancianos. Objetivos: Describir las características sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Nevertheless, among older adults, the prevalence of therapeutic non-adherence is as high as 50% [15-19]. Furthermore, about 20% of these cases have prescribed medications, which they do not take [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, among older adults, the prevalence of therapeutic non-adherence is as high as 50% [15-19]. Furthermore, about 20% of these cases have prescribed medications, which they do not take [20].…”
Section: Introductionmentioning
confidence: 99%
“…2 Further, comorbidity, polypharmacy, and lack of awareness about drugs cause poor medication adherence among the elderly. 12,38,76,77 In this study, it was also shown that medication adherence was significantly lower among the elderly suffering from CVD and depression compared with the elderly who showed no depression symptoms. A negative and mild-to-moderate relationship was also found between the mean score of depression and medication adherence in the researched elderlies.…”
Section: Discussionmentioning
confidence: 49%
“…Meanwhile, around 30% of the elderlies suffering from depression show no apparent symptoms 2 . Further, comorbidity, polypharmacy, and lack of awareness about drugs cause poor medication adherence among the elderly 12,38,76,77 . In this study, it was also shown that medication adherence was significantly lower among the elderly suffering from CVD and depression compared with the elderly who showed no depression symptoms.…”
Section: Discussionmentioning
confidence: 60%
“…(13) Intervenções para melhorar a adesão terapêutica é um importante subsídio para a melhoria da saúde da população idosa, com reflexos no aumento da qualidade de vida, redução das recorrências aos serviços de urgência e de hospitalização. (19) Estudo com 55 idosos integrantes de equipes domiciliares de cuidados continuados do Sul de Portugal apontou que 40 (72,7%) deles não aderiram à terapêutica medicamentosa. Apesar de não se verificar associação estatística, fatores como baixo nível de rendimento, viver sozinho e ter depressão podem ter influenciado no resultado (19) e, assim, servir de alerta para os profissionais que planejam a alta hospitalar.…”
Section: Idiscussãounclassified